Effect of L-citrulline intake on intermittent short-time high-intensity exercise performance in male collegiate track athletes - Naoko Terasawa; Kenta Nakada (Japanese Society of Physical Fitness and Sports Medicine, 2019)
Enhanced exercise performance and anti-fatigue effects following L-citrulline (Cit) intake have been reported in resistance training and endurance exercise, but not in intermittent short-time high-intensity exercise. Therefore, the effect of Cit intake on intermittent short-time high-intensity exercise performance in collegiate athletes was investigated. A double-blind, placebo-controlled crossover trial was performed using nine male collegiate track athletes (age 20.9 ± 1.6 years). Each participant ingested either Cit or a placebo (3 g [grams]/day) for 7 days and underwent Wingate test using a bicycle ergometer on days 0 and 7 performed three times using a pedaling load of 7.5% of the participant's weight for 30 s (seconds) at full power. As for the results, Cit intake significantly increased the change in mean power output, pedaling speed per 5 s, and power output per 5 s (Δday 7 - 0) during pedaling as well as the change in oxygen consumption derived by analysis of expired gas. The amount of change in the rate of perceived exertion during exercise significantly decreased, and the amount of change in serum nitrite/nitrate (NOx) (Δday 7 - 0) post-exercise was significantly increased compared to that of pre-exercise by Cit intake. These results suggested that Cit intake of 3 g/day for 7 days may have enhanced exercise performance and anti-fatigue effects on intermittent short-time high-intensity exercise in male collegiate track athletes.